Development of polyethersulfone (PES)/silver nanoparticles (AgNPs)/polyethylene glycol (PEG) nanofiltration membrane - Johary, F.; Jamaluddin, N.A.; Rohani, R.; Hassan, A.R.; Sharifuddin, S.S.; Isa, M.H.M. (2018)
Nanofiltration is a membrane-based separation process that has been used widely in the separation and purification fields for various applications such as dye desalting, applications of water soening, pharmaceuticals and wastewater treatment. In this research, polyethersulfone (PES), polyethylene glycol (PEG), Pluronic F108 and silver nanoparticles (AgNPs) nanofiltration membrane was prepared using casting solution technique with N-methyl-2-pyrrolidone (NMP) was used as a solvent. The effects of Pluronic F108 and silver nanoparticles (AgNPs) concentrations in the casting solutions on the membrane performance/properties were also studied. The membrane pure water permeation (PWP) and salt rejection tests were carried out for membrane performance analysis. Scanning electron microscopy (SEM) was used for the membrane morphology characterization. Fourier transform infrared spectroscopy was utilized to identify functional groups in the membrane. Membrane with 2.0 wt.% of Pluronic F108 and 0.05 wt.% of AgNPs showed the best performances for both PWP (40.89 L/m(2)h) as well as permeation flux of salts solution of NaCl (43.95 L/m(2)h), Na2SO4 (21.16 L/m(2)h), MgCl2 (26.46 L/m(2)h) and MgSO4 (20.41 L/m(2)h). All fabricated membranes with different formulation of dope composition obtained high salts rejection in the range of 79% to 91%. SEM images showed addition of AgNPs has improved fabricated membrane morphology with higher pore density and larger macro-void structure.